Protective Effects of Rosmarinic Acid and Epigallocatechin Gallate Against DoxorubicinInduced Cytotoxicity and Genotoxicity in CHO-K1 Cells - Helvacioglu, Sinem; Hamitoglu, Muhammed; Yildirim, Ecem; Vural Korkut, Senay; Yaba, Aylin; Aydin, Ahmet (GALENOS PUBL HOUSE, 2024)
Objectives: The chemotherapeutic drug doxorubicin (DOX) affects not only cancer cells but also healthy cells in an undesirable manner. The purpose of this study was to investigate the protective roles of rosmarinic acid (RA) and Epigallocatechin gallate (EGCG) alone and in combination against DOX-induced oxidative stress, cytotoxicity, and genotoxicity in healthy cells. In addition, this study evaluated the expression of the mammalian target of rapamycin (mTOR) protein in the Chinese hamster ovary cell line (CHO-K1). Materials and Methods: Cell viability was analyzed using the WST-1 cytotoxicity assay. mTOR expression in the CHO-K1 cell line was determined by western blotting. DNA damage was analyzed using a comet assay. Reactive oxygen species (ROS) levels were determined microscopically using the dihydroethidium staining method. Results: RA demonstrated superior protective effects against DOX-induced cytotoxicity compared to EGCG. Epigallocatechin gallate and RA did not exert genotoxic effects, but DOX increased genotoxicity in CHO-K1. Neither RA nor EGCG exhibited genotoxic effects; however, DOX significantly increased genotoxicity in CHO-K1 cells. Both RA and EGCG markedly reduced DOX-induced genotoxicity, as confirmed by the comet assay. In the DOX-treated group, the expression of mTOR protein was notably suppressed. EGCG further reduced mTOR protein levels when administered alone or in combination with DOX, whereas RA did not exhibit a similar effect. RA decreased intracellular generation of ROS in CHO-K1 cells. However, at high concentrations, Epigallocatechin gallate did not protect against oxidative stress and cell damage due to its prooxidant properties. Conclusion: Epigallocatechin gallate and RA are promising plant-derived active components. Another important point is the evaluation of the safety of herbal products. It should be considered that herbal products may increase the toxicity of chemotherapeutic agents.
Keywords: DNA damage; comet assay; Western blot; mTOR; WST-1 assay; oxidative stress; GREEN TEA CATECHINS; (-)-EPIGALLOCATECHIN GALLATE; CANCER; DAMAGE; Pharmacology & Pharmacy